(untitled) (Training and Practice : Journal of Educational Sciences, 2012)
EdTWIN is an international project of the West Hungarian University Apáczai Faculty having the point of getting acquainted with neighbouring countries and their establishments of higher education, to build and maintain connections. The project has many programmes: one of them, CentroSCHOOLING gave the possibility to Apáczai students and teachers of special education to visit and examine the professional institutional work in Vienna special education schools. This one week professional practice in the Austrian capital gave the opportunity to our students to meet colleagues learning and working in a different education system. Not only the first hand experiences in methodology but also the practice of German as a foreign language was highlight of the programme. The students of the Apáczai Faculty also worked out an extensive and detailed professional material that served as base for common work in Győr and Vienna and was first presented to Austrian students in Vienna. After the first week in Vienna, the Austrian students spent one week in Győr.